Can neck circumference measurement predict insulin resistance than waist circumference? - Seremet Kürklü, Nilgün; Bilgiç, Pelin; Kaner, Gülşah (Progress in Nutrition, 2018)
Objective: There is a high correlation between insulin resistance and abdominal obesity. Although there are many anthropometrical measurements to determine obesity, neck circumference measurement has started to be used in recent years in addition to other anthropometrical measurements. This research has been conducted in order to assess the relationship between the neck circumference and insulin resistance parameters of the individuals with insulin resistance diagnosis. Material-Method: This study was conducted with 101 individuals who applied to endocrinology or internal medicine clinics, and were diagnosed with insulin resistance. Demographical features of the individuals were questioned with a questionnaire form; and anthropometrical measurements such as body weight, height, waist, and neck circumference were taken by the researcher. The body compositions of the individuals were evaluated with the Bioelectrical Impedance Analysis (BIA). HOMA-IR indexes were calculated by recording the fasting blood glucoses and fasting plasma insulin values from the files of the individuals. Results: According to World Health Organization criteria, 21.2% of the participating women, and 18.7% of the men were overweight; 76.5% of the women, and 81.3% of the men were obese. The mean neck circumference was 38.1±2.4 cm in women, while it was 44.9±3.1 cm in men. It was determined that there was a high correlation between the neck circumference and the other anthropometrical measurements of women; and that there was a strong positive relationship between the neck circumference and body weight, waist circumference, and fat-free body mass of men. A significant relationship was identified between neck circumference measurement and fasting plasma insulin, and HOMA-IR, which are one of the insulin resistance parameters. Conclusion: It was observed that two thirds of the individuals with insulin resistance were obese, and all of their waist and neck circumference levels were high that propose risk for metabolic diseases. A positive but low correlation was found between neck circumference and all other anthropometrical measurements, fasting plasma insulin and HOMA-IR index, which are indicators of insulin resistance. Therefore, neck circumference, too, may be an anthropometrical measurement that can be used in diagnosing the insulin resistance as an indicator of obesity just like waist circumference and Body Mass Index.